Evaluating the Returns to Education and On-The-Job Training in Informal Sector Employment - Yusuf, Jamiu Adeniyi; Ibrahim, Muinat Abiodun (Aktual: Jurnal Pengabdian Kepada Masyarakat, 2025)
Background of the Study: A significant section of the workforce in many developing nations is employed in the unorganized sector, which is frequently marked by volatility and lax regulation. Developing equitable and sustainable labor and development strategies requires an understanding of how education and vocational training affect job outcomes and wages in this sector.Aims and Scope of Paper: The purpose of this paper is to investigate the financial benefits that informal workers receive from education and on-the-job training. It also examines research trends, significant authors, and thematic areas of interest. Methods: A bibliometric analysis using VOSviewer was conducted to support a qualitative systematic review that was carried out utilizing the PRISMA 2020 methodology. This method made it possible to map academic papers quantitatively and include qualitative insights.Results: Although the effects of formal education and job-specific training vary by location, gender, and educational quality, they generally increase the salaries, employability, and job stability of informal workers. Bibliometric analysis shows uneven regional presence and growing research clusters.Conclusion: Programs for education and training that are targeted, equity-driven, and adapted for the informal sector are essential. Particularly in low- and middle-income nations, such programs can close the gap in human capital, raise individual incomes, strengthen labor resilience, and advance social justice and overall economic stability.